Direitos de terceira dimensão: a tutela do direito do consumidor no Brasil por meio das ações coletivas - Guimarães, Alexandre José (2015)
The objective of this thesis is to set the mechanism by which the state will judicially protect the Brazilian consumer, and this way put into power what is stated in the 5th Article Item XXXII of the Brazilian Federal Constitution. A wide bibliographic research was used for the preparation of the text, applying the deductive method for the achievement of the conclusions. The text was divided into seven chapters, as follows: 1) Fundamental rights in 1988 Constitution; 2) Consumers Right as third dimension fundamental right; 3) Defense of consumers rights in Brazil; 4) Ineffectiveness of State in the defense of consumers rights; 5) Microsystem of Consumers Right Code; 6) Class action in Brazil; 7) Conclusion. The initial concern was the ineffectiveness of State in the defense of consumer s rights, particularly before the public numbers of National System of Consumer's Defense - NSCD, which shows the reduced numbers of Procons in Brazil in contrast with high number of consumer's lawsuits. In this scenario, the necessary doubt about the correct state structure for consumer's defense arises, for millions of individual demands could be substituted with class actions, thereby reducing the pressure on the Judiciary Power and increasing the social response. The application of the class actions proves to be more appropriate with judicial defense of consumer's rights, most importantly in face of being third dimension fundamental right, thereinafter. The correct approach of fundamental rights in the Brazilian Constitution and showing those rights as fundamentals of third dimension were shown therein, followed by the analysis of state defense of consumers rights, both judicially and non judicially. In the sequence the microsystem of Consumers Defense Code was thoroughly assessed with the purpose of showing the judicial defense of consumer's rights, although it can individually performed, it must be made by class actions by the State, organs and entities. The next step was the assessment of the Brazilian Class Actions as a way to assure the effectiveness of the fundamental right ruled by 5º, XXXII, of 1988 Brazilian Federal Constitution